Estafet Writing Method to Improve Arabic Writing Skills Outcomes: Experimental Study on Indonesian Middle School Students - Nur Laila Sa’idah; Sholikah Mi’rotin; Fentin Ria Agustin (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2021)
One of the language skills that require a process of practicing, learning, and proper techniques for teaching students in writing. By intensive practicing and studying, students become skillful faster. It seems difficult for students to compile their writing without making careful planning before writing. Many students cannot express their opinion because the teacher does not teach them properly. Teaching writing with monotone techniques inhibits students to get the ideas provided by the teacher during the writing learning process. This research focused on the methods used by the teacher in Maharah Kitabah (writing skills), which was at relay writing method (chain writing). The research method used was experimental, that data was collected by observation and test. Then, the data were analyzed by using the N-Gain. From the results of the N-Gain test, the average score of the pre-test and post-test scores has increased by a percentage of 59%. While the average score obtained from the acquisition of the N-gain value is 0.72, therefore, the category was high. This result proves that the estafet writing method can improve Arabic writing skills outcomes.